Accurate quantification of apoptosis progression and toxicity using a dielectrophoretic approach. Issue 23 (24th October 2016) - Henslee, Erin A.; Torcal Serrano, Ruth M.; Labeed, Fatima H.; Jabr, Rita I.; Fry, Christopher H.; Hughes, Michael P.; Hoettges, Kai F.
Abstract : A rapid, low-cost and label-free method of cell analysis compares favorably to Annexin-V, MTT and trypan blue for assessment of apoptosis and IC50 . Abstract : A loss of ability of cells to undergo apoptosis (programmed cell death, whereby the cell ceases to function and destroys itself) is commonly associated with cancer, and many anti-cancer interventions aim to restart the process. Consequently, the accurate quantification of apoptosis is essential in understanding the function and performance of new anti-cancer drugs. Dielectrophoresis has previously been demonstrated to detect apoptosis more rapidly than other methods, and is low-cost, label-free and rapid, but has previously been unable to accurately quantify cells through the apoptotic process because cells in late apoptosis disintegrate, making cell tracking impossible. In this paper we use a novel method based on light absorbance and multi-population tracking to quantify the progress of apoptosis, benchmarking against conventional assays including MTT, trypan blue and Annexin-V. Analyses are performed on suspension and adherent cells, and using two apoptosis-inducing agents. IC50 measurements compared favourably to MTT and were superior to trypan blue, whilst also detecting apoptotic progression faster than Annexin-V.